De la conceptualización pedagógica a la construcción de una pedagogía crítica para la atención a la diversidad - Paulette Barberousse-Alfonso; Luz Emilia Flores-Davis; Rafael Estéban Jiménez-Corrales; Irma Zúñiga-León (Universidad Nacional, Costa Rica, 2004)
This paper presents and justifies the basic concerns aroused by our new curriculum design; concerns that are related with the treatment given to diversity issues from the perspective of critical pedagogy in teacher training programs. We address here an important problem and issue that constitutes the basic orientation of the Graduate Program on Pedagogy with an Emphasis on Diversity in Educational Processes, which is offered by the Division on Elementary Education of the Universidad Nacional's School of Education (Spanish acronym, CIDE).